Comparison of disruption mitigation from shattered pellet injection with massive gas injection on J-TEXT. (28th October 2021) - Li, Y.; Chen, Z.Y.; Yan, W.; Wei, Y.N.; Tong, R.H.; Lin, Z.F.; Li, W.; Bai, W.; Wang, N.C.; Li, D.; Chen, Z.P.; Jiang, Z.H.; et al.
Abstract: The mitigation of disruption damage is essential to the safe operation of a large-scale tokamak. In order to achieve the safe operation of ITER, the shattered pellet injection (SPI) has been considered as a primary measure of disruption mitigation. A dedicated argon SPI system, focusing on disruption mitigation has been designed for the J-TEXT tokamak. In the J-TEXT SPI system, a pure argon pellet can be formed in the freezing tube, then separated from the tube and accelerated by a punch mechanism. The pellet can be injected with a speed of 150–300 m s −1 . The performance of disruption mitigation by Ar SPI has been compared with Ar massive gas injection (MGI). The cooling process observed from the ECE indicates that the SPI has deeper deposition, with the cold front that can reach the q = 1 rational surface in case of SPI, but stops at the q = 2 profile in MGI. The increase of core plasma density during a fast shutdown is higher than that with Ar MGI, which proves a deeper penetration of SPI. In disruption, the magnetohydrodynamic (MHD) activities, measured at the Mirnov coils, have similar behavior in both MGI and SPI shots. The m / n = 2/1 mode dominates the MHD activities from the penetration to the end of the thermal quench (TQ). Subsequently, in the current quench (CQ) phase, the m / n = 3/1 mode grows to become the dominant mode. The radiation power is much stronger in the SPI shot. The radiation asymmetry is compared in the two plasma disruption mitigation methods. Changing the pellet velocity can effectively adjust the TQ process and CQ rate, which can achieve a higher impurity assimilation rate when the pellet velocity increases in a certain range.